2017
DOI: 10.1007/s11145-017-9727-3
|View full text |Cite
|
Sign up to set email alerts
|

The impact of image characteristics on written naming in adults

Abstract: International audienceThe present study was aimed at investigating whether and how image characteristics influence written naming performance in adults. In three different sessions, participants had to quickly write down the names of pictured objects on a graphic tablet. Across sessions, the picture format was different, but the to-be-named objects were the same: There were black-and-white pictures (Snodgrass & Vanderwart’s [SV] 1980 drawings), grayscale and colored pictures of the SV drawings as provided by R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…Third, the material had to be pictures in black lines on white backgrounds such as those used by Snodgrass and Vanderwart (1980). Recently, Bonin, Méot, Laroche, Bugaiska, and Perret (2017) suggested that the cognitive processes underpinning object naming could, at least in part, intervene differently depending on whether colored or black-and-white pictures are used. The differences in picture formats can add noise in analyses.…”
Section: Studies Included In Analysesmentioning
confidence: 99%
“…Third, the material had to be pictures in black lines on white backgrounds such as those used by Snodgrass and Vanderwart (1980). Recently, Bonin, Méot, Laroche, Bugaiska, and Perret (2017) suggested that the cognitive processes underpinning object naming could, at least in part, intervene differently depending on whether colored or black-and-white pictures are used. The differences in picture formats can add noise in analyses.…”
Section: Studies Included In Analysesmentioning
confidence: 99%
“…Primary school children are a sector of the population that requires well-controlled visual stimuli and one with which pictures are widely used in educational materials and assessment instruments (e.g., test WISC-IV; Wechsler, 2003). In addition, data collection through a written naming task facilitates conducting research with large groups of participants efficiently (e.g., Berman et al, 1989; Bonin et al, 2019). It also reduces significantly the time and cost of the experiments with children, as long as children have the basic spelling skills that allow them to write words fluently.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, it has been extensively studied how color and surface details affect object recognition in drawings and in photographs, separately. For example, it has been shown that color improves name agreement (Rossion & Pourtois, 2004), memorization (Vernon & Lloyd-Jones, 2003), and naming speed of objects (e.g., Bonin et al, 2019; Rossion & Pourtois, 2004) by comparing naming performance when using black-and-white, grayscale, and colored drawings; and identification and memorization of objects by comparing black-and-white photographs and colored photographs (e.g., Lloyd-Jones & Nakabayashi, 2009; Uttl, Graf & Santacruz, 2006). In a meta-analysis, Bramão et al (2011) examined the effect of color on object recognition, mainly using naming tasks, in 35 experiments involving 1,535 adult participants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, it has been extensively studied how color and surface details affect object recognition in drawings and in photographs, separately. For example, it has been shown that color improves name agreement (Rossion & Pourtois, 2004), memorization (Vernon & Lloyd-Jones, 2003), and naming speed of objects (e.g., Bonin, Méot, Laroche, Bugaiska, & Perret, 2019;Rossion & Pourtois, 2004) by comparing naming performance when using black-andwhite, grayscale, and colored drawings; and identification and memorization of objects by comparing black-and-white photographs and colored photographs (e.g., Lloyd-Jones & Nakabayashi, 2009;Uttl, Graf, & Santacruz, 2006). In a meta-analysis, Bramão, Reis, Petersson, and Faísca (2011) examined the effect of color on object recognition, mainly using naming tasks, in 35 experiments involving 1,535 adult participants.…”
Section: Introductionmentioning
confidence: 99%